Analysis of the main indicators and risk factors of ultrasonic shear wave elastography for the diagnosis of osteoarthritis among adults - Zhang, Jiong; Zheng, Xiaozuo; Zhao, Ying (Frontiers in Medicine, 2024)
Objective This study was conducted to explore the main indicators of ultrasonic shear wave elastography (SWE) for the diagnosis of osteoarthritis (OA) and its influencing factors. Methods We collected 910 patients between January 2018 and November 2023 from the department of ultrasound, Third Hospital of Hebei Medical University. Logistic regression was used to analyze the effects of age, gender, body mass index (BMI), smoking, alcohol, hypertension and diabetes on the diagnosis of OA by SWE. Results The results showed that medial meniscal projection distance (MMPD) and OA had a positively correlated dose–response relationship (OR = 2.12, 95%CI (1.53, 3.95), trend p < 0.05). Also, medial meniscus elastometry (MME) had a positive dose–response correlation with OA (OR = 8.98, 95%CI (3.89, 11.52), trend p < 0.05). In addition, regarding the analysis of factors influencing the diagnosis of OA, the risk of OA was significantly higher in the older age group [OR = 1.11, 95%CI (1.01, 1.25)], and the risk of diagnosis in OA was high in the high BMI group [OR = 1.8, 95%CI (1.23, 3.01)]. Conclusion In diagnosing OA, MMPD and MME can be used as reliable indicators, while people of advanced age and high BMI have a high possibility diagnosed with OA.